2011
DOI: 10.1111/j.1753-6405.2011.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Community screening for cardiovascular risk factors and levels of treatment in a rural Māori cohort

Abstract: Māori are the indigenous people of New Zealand (NZ), comprising approximately 15% of the national population. A major disparity exists between Māori and non-Māori in cardiovascular mortality, which remains the leading cause of premature death and disability in New Zealand.1,2 Furthermore, recent health statistics indicate that those living in rural areas are worse off than urban New Zealanders, including for prevalence of ischaemic heart disease.3 Rural Māori have a shorter life expectancy than urban Māori, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…The Hauora Manawa/Community Heart Study is a cohort study of heart disease in New Zealand, based on random selection from electoral rolls, sampled to be representative of the age and gender profiles within each participating Māori community. Full details of the methodology, sample selection, recruitment and interviewing processes are published elsewhere . In brief, a total of 751 participants aged 20 to 64 years was recruited by random selection, stratified by age and gender, from the electoral roll for Wairoa District and for Christchurch City.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hauora Manawa/Community Heart Study is a cohort study of heart disease in New Zealand, based on random selection from electoral rolls, sampled to be representative of the age and gender profiles within each participating Māori community. Full details of the methodology, sample selection, recruitment and interviewing processes are published elsewhere . In brief, a total of 751 participants aged 20 to 64 years was recruited by random selection, stratified by age and gender, from the electoral roll for Wairoa District and for Christchurch City.…”
Section: Methodsmentioning
confidence: 99%
“…Full details of the methodology, sample selection, recruitment and interviewing processes are published elsewhere. 14,15 In brief, a total of 751 participants aged 20 to 64 years was recruited by random selection, stratified by age and gender, from the electoral roll for Wairoa District and for Christchurch City. Participants for the Mā ori samples were selected from among those who identified as being of Mā ori descent on the roll and who also self-identified at interview as being of Mā ori ethnicity.…”
Section: Methodsmentioning
confidence: 99%
“…11 No studies to date have compared cardiovascular health and risk factors between rural and urban M aori communities, and the only previous study of cardiovascular health in rural M aori was conducted 50 years ago. 12 We have recently reported high levels of both diagnosed and undiagnosed CVD risk factors, especially hypertension, dyslipidaemia and diabetes in a rural M aori community, 13 with several major risk factors at higher levels than those reported than either national statistics or for Auckland City M aori. To understand how CVD risk factors differ between diverse localities across New Zealand, we have compared the cardiovascular risk profiles of two regionally distinct rural and urban M aori communities and a matched urban comparator cohort of non-M aori to identify risk factors in common and those that differ among these communities.…”
Section: Introductionmentioning
confidence: 91%
“…13 In brief, all participants completed an interviewer-administered questionnaire providing demographic, personal and family medical history, current medications, smoking status recorded as current, ex-smoker (quit more than 12 months) or never-smoker, alcohol consumption, physical activity levels (physically active defined as 'at least 30 min of moderate or vigorous physical activity on 5 or more days of the week') and socioeconomic data. Blood pressure was recorded (two measurements, seated, at least 20 min apart), height, weight, waist and hip measurements were taken and body mass index (BMI) was calculated.…”
Section: Screening Clinicsmentioning
confidence: 99%
“…They found that rural Māori were at greatest risk of CVD because of higher levels of; obesity, dyslipidaemia, hypertension, smoking, type 2 diabetes and hyperuricaemia, than urban Māori, and urban nonMāori ( Figure 6) [54]. A number of researchers have concluded that the development of an integrated healthcare programme is required to address the increased risks of CVD in rural and urban Māori that is sensitive to their cultural perspective of health [54][55][56]. While interventions that focus upon such risk factors are important they will fail to fully address the ethnic inequities that exist in New Zealand healthcare unless the socioeconomic inequities such as poverty are addressed first [33].…”
Section: Cultures Apartmentioning
confidence: 99%